Impact of covid-19 on the performance of Central American firms: A first review. (2021)
The coronavirus pandemic has caused a disruption in global production chains. Therefore, it is important to examine the impact of this phenomenon on companies from different economic sectors, especially in countries with a lower response capacity to face this public health emergency. With that in mind, the objective of this work is to determine how the covid-19 pandemic has affected business performance in four Central American countries. Using longitudinal data from the World Bank business survey, a differences model was implemented in order to estimate the impact of this pandemic, considering both internal and external characteristics. According to our findings, the studied four-month impact of the pandemic was significant, with about 2% of businesses in the studied countries closing permanently and 60% temporarily. Sales and sales per employee dropped about 30%, with the situation being worse for companies that closed temporarily due to restrictions. However, the immediate response of governments through tax credits and incentives has been well geared to meeting short-term liquidity needs of firms.